The Use of Picture in Teaching Speaking at the Class VIII SMPN 1 Kendari - Restipa, Indri; Syahriani, Ririn; Rusli, Tri Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of using picture media in learning English speaking skills for eighth grade students of SMPN 1 Kendari. This study uses a quantitative approach with a pre-experimental One-Group Pretest–Posttest Design involving 32 students of grades VIII-8 selected through purposive sampling techniques. Data were collected through oral tests assessed based on aspects of fluency, vocabulary, grammar, pronunciation, and comprehension, then analyzed using descriptive and inferential statistical tests with the help of the SPSS program. The results of the study showed a significant increase in students' speaking skills after learning using picture media, with an average score increasing from 11.81 in the pre-test to 21.19 in the post-test. The results of the Wilcoxon test showed a significance value of 0.000 0.05, which means there was a significant difference between the results of the pre-test and post-test. The use of visual media also positively impacts students' motivation and confidence in speaking English, as well as creating a more active and enjoyable learning environment. Thus, visual media has proven effective as a relevant learning strategy for improving students' speaking skills at the junior high school level.